Association of Baseline Serum Levels of CXCL5 With the Efficacy of Nivolumab in Advanced Melanoma - Fujimura, Taku; Sato, Yota; Tanita, Kayo; Lyu, Chunbing; Kambayashi, Yumi; Amagai, Ryo; Otsuka, Atsushi; Fujisawa, Yasuhiro; Yoshino, Koji; Matsushita, Shigeto; Uchi, Hiroshi; Yamamoto, Yuki; et al. (Frontiers in Medicine, 2019)
Anti-programmed cell death protein 1 (PD1) antibodies are in wide use for the treatment of various cancers. PD1 antibody-based immunotherapy, co-administration of nivolumab and ipilimumab, is one of the optimal immunotherapies, especially in advanced melanoma with high tumor mutation burden. Since this combined therapy leads to a high frequency of serious immune-related adverse events (irAEs) in patients with advanced melanoma, biomarkers are needed to evaluate nivolumab efficacy to avoid serious irAEs caused by ipilimumab. This study analyzed baseline serum levels of CXCL5, CXCL10, and CCL22 in 46 cases of advanced cutaneous melanoma treated with nivolumab. Baseline serum levels of CXCL5 were significantly increased in responders compared to non-responders. In contrast, there were no significant differences of baseline serum levels of CXCL10 and CCL22 between responders and non-responders. These results suggest that baseline serum levels of CXCL5 may be useful as a biomarker for screening patients with advanced cutaneous melanoma most likely to benefit from anti-melanoma immunotherapy.